Hubungan Keterlibatan Ayah Terhadap Preferensi Pemilihan Pasangan Hidup pada Anak Perempuan di Yogyakarta - Renita Satian; Andhita Dyorita Khoiryasdien (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
One of the tasks of early adult development is to find and find a life partner, where each individual in determining his life partner must consider the personality of his partner according to what he wants. Preference for choosing a life partner is a process carried out to determine decisions related to choosing a life partner which is carried out in a complex and very important way at least once in a lifetime. In girls in the process of their life development, father involvement has an important role in every process of their life, the purpose of this study is to determine whether there is a relationship between father involvement and preferences for choosing a life partner for girls. The research method used is quantitative correlational research. The results of the study showed that there was a positive relationship between father involvement and preferences for choosing a life partner for girls, this is evidenced by the Person Correlation Product Moment value showing r count (0.605) with significance = 0.000 (p <0.05) which indicates the relationship between the two variabels is quite strong.